Another Hafiz' ghazal translated by Shakerim (Journal of Oriental Studies, 2016)
In this article the author has examined another gazelle of Hafiz, the great Persian poet, which was translated by Shakarim Kudaiberdiuly and has analyzed its original text with its Kazakh translation.
Keywords: ghazal; sufi; prayer; truth; the tree cider